’Somel’ and ’Rosalina’ – new yellow-flesh nectarines - Ojima, Mário; Dall’Orto, Fernando A. Campo; Barbosa, Wilson; Tombolato, Antonio F.C.; Rigitano, Orlando; Castro, Jairo L.; Santos, Rui R. (Pesquisa Agropecuaria Brasileira, 2014)
’Somel’ (IAC N 1974-7) and ’Rosalina’ (IAC N 3074-49) are two new low chilling nectarine selections adapted to the mild winter climatic conditions prevailing in the State of São Paulo. They are the result of the nectarine breeding work started at the Instituto Agronômico, Campinas (IAC), Campinas, SP, Brazil, in 1970, with crosses between some local peach cultivars and nectarine selections introduced from Florida, USA. ’SomeI’ parentage is ’Ouromel’ x ’Sunred’ F2 self-pollinated, highy-sweet, with low acidity, while ’Rosalina’ is ’Real’ x Fla. 44-28 F2 open pollinated and highly-acidulous sweet. Both are yellow flesh, clingstone nectarines, of good dessert quality.